Proportional Representation and Right-Wing Populism: Evidence from Electoral System Change in Europe - Becher, Michael; Menéndez González, Irene; Stegmueller, Daniel (Cambridge University Press, 2022)
How much do electoral institutions matter for the rise of populist parties? Evidence on this question is mixed, with some scholars arguing that the role of electoral rules is small. We provide new evidence for the impact of electoral system change. The UK's adoption of a proportional electoral system for European elections in 1999 provides a unique opportunity to study the link between electoral rules and the ascendancy of right-wing populist parties. Employing both synthetic control and difference-in-difference methods, we estimate that the electoral reform increased the vote share of right-wing populists by about 12 to 13.5 percentage points on average. During a time when populism was rising across Europe, the reform abruptly shifted populist votes in the UK above the European trend and above more plausible comparison cases. Our results also imply that caution is needed when empirical results based on partial reforms are extrapolated to electoral system change.
Keywords: Populism; Electoral rules; Electoral reform; European Union; Synthetic control; 59 Ciencia Política::5905 Vida política::5905.02 Comportamiento político; ODS 10 - Reducción de las desigualdades